Persistent lesions in endodontics (Research, Society and Development, 2022)
Apical periodontitis is mainly caused by both microrganisms and their virulence factors. This process can be associated with the survival of its causative agents due to coronary microleakage after chemical-mechanical preparation and filling. However, persistent apical periodontitis can be solved through endodontic retreatment or apical surgery. In addition, its association with systemic diseases has been reported in different studies. The aim of the current study is to perform a literature review on studies about apical periodontitis, with emphasis on current microbial profile and treatment modalities. Studies have shown significant heterogeneity in microbial profile, as well as likely associations with some diseases. Moreover, they have mainly focused on investigating persistent apical periodontitis based on molecular biology. It was possible concluding that, although Enterococcus faecalis is the species most often associated with failure in endodontic treatments, the incidence of other microrganisms, such as Candida albicans, Streptococcus spp., Actinobacteria spp., has been observed at the same, or even at higher, level than that of E. faecalis. Retreatment should always be taken into consideration as the first option to treat morbidities, although surgery can be performed if retreatment is not successful.